Multiple benign tumours in the oral and maxillofacial region of an adolescent. (11th July 2013) - Jeganathan, S.; Gerber, B.; Curtis, A.; Saeed, N.
Abstract Multiple tumours occurring in the oral and maxillofacial region of paediatric patients are extremely rare. This case report describes the successful management of the first documented case of synchronous pleomorphic adenoma of the submandibular gland and Schwannoma of the tongue in a 16‐year‐old girl.